Unlocking the Advantages Of N-Vinyl-2-Pyrrolidone as A Superior Alternative to Formalin in Cadaver Preservation: A Comprehensive Review - Gehlot, Dhruv; Srivastava, Stuti (Journal of Biomedicine and Biochemistry, 2023)
Background The field of anatomical preservation has witnessed a continual evolution of embalming techniques, with an increasing focus on exploring alternative meth- ods that address both structural integrity and safety con- cerns.Purpose This research endeavours to delve into the diverse landscape of alternative embalming method N- vinyl-2-pyrrolidone (NVP) embalming, emphasizing the need for a thorough evaluation of various factors to deter- mine their suitability for application in educational and research institutions.